Level of Orthographic Knowledge Helps to Reveal Automatic Predictions in Visual Word Processing - Huang, Zehao; Yang, Shimeng; Xue, Licheng; Yang, Hang; Lv, Yating; Zhao, Jing (Frontiers in Neuroscience, 2022)
The brain generates predictions about visual word forms to support efficient reading. The “interactive account” proposed by Price and Devlin (2011) suggests that the predictions in visual word processing can be strategic or automatic (non-strategic). Strategic predictions are frequently demonstrated in studies that manipulated task demands, however, few studies have investigated automatic predictions. Orthographic knowledge varies greatly among individuals and it offers a unique opportunity in revealing automatic predictions. The present study grouped the participants by level of orthographic knowledge and recorded EEGs in a non-linguistic color matching task. The visual word-selective N170 response was much stronger to pseudo than to real characters in participants with low orthographic knowledge, but not in those with high orthographic knowledge. Previous work on predictive coding has demonstrated that N170 is a good index for prediction errors, i.e., the mismatches between predictions and visual inputs. The present findings provide unambiguous evidence that automatic predictions modulate the early stage of visual word processing.